O necessário enfoque na hermenêutica e nas humanidades no ensino do direito: implicações sobre a educação jurídica atual - Mendes, Ana Isabel (2023)
This work presents an investigation into legal education, with the aim of find the main gaps that trigger the crisis in the application of Law. The methodology used was bibliographical research, and the results found as main causes are dogmatics, positivism and neoliberalism, showing that influenced the current legal model of plasticization and "manualization" of teaching and deviation from the purposes of Law, which bowed to economic and profit purposes. You results are relevant to legal education and Law as a whole, providing subsidies for resolving problems related to the distance between legal theory and practice and failure to fulfill the purpose public law, when bowing to economic aspects. This study highlights the importance of a structural reformulation of legal education, with greater focus on hermeneutics and the humanities, providing insights for possible reformulations in legal education. It is concluded that legal education deserves to be restructured to the preservation of the Law, including the way in which the OAB's selection processes and public competitions are held, which ask questions that are irrelevant to the role of the jurist. It also leads to the need to review the importance of the humanities and their transversality in other disciplines, in addition to to emphasize hermeneutics as a necessary and essential technique for good application of the Law, which passes through the scrutiny of the interpreter. These conclusions contribute for effective and liberating teaching, focused on autonomy, self-management, critical reasoning and the efficient application of Law.